Meso-meso 1,3-Bis(E-vinyl)azulene bridged tetrathiaoctaphyrins: synthesis and spectroscopic and theoretical characterization - Sahoo, Sumit; Velmurugan, Gunasekaran; Comba, Peter; Rath, Harapriya (Organic chemistry frontiers, 2023)
The expedient syntheses, spectroscopic analysis, solid state structural proof and theoretical study of structural variants of strongly aromatic(antiaromatic) meso-meso 1,3-bis(E-vinyl)azulene bridged(nonbridged) tetrathiaoctaphyrins exhibiting strong NIR absorption are reported. The lack of participation of the 1,3-bis(E-vinyl)azulene internal bridge in the global π-conjugated network of tetrathiaoctaphyrins led to the loss of effective dual macrocyclic conjugation pathways, which has been fully supported by thorough DFT studies. AICD, NICS, HOMA, MCI, AV1245 index, AVmin, WBI and ELF analyses have been carried out to explain the nature and origin of the major [34π]/[36π] single-conjugated Hückel aromaticity(antiaromaticity) in detail for all the three octaphyrins with(without) the meso-meso 1,3-bis(E-vinyl)azulene bridge.